Enumeration of the microbiota and microbial metabolites in processed cassava products from Madagascar and Tanzania - Abass, A.; Adegoke, G.O.; Awoyale, W.; Gaspar, A.; Mlingi, N.; Andrianavalona, V.; Sulyok, M.; Mneney, A.; Ranaivoson, L.R. (Elsevier, 2019)
Cassava processing practices vary among communities and countries with implications for food safety. The study examined the microbiota and microbial metabolite profiles of 126 samples of sun-dried cassava products: grits, improved chips, improved flour, kivunde, and makopa from Tanzania, and mangahazo maina from Madagascar. All samples were free of Salmonella spp. Only 12.5% makopa, 6.7% of mechanically processed flour, and 25% of chips conformed to yeast/mold regulatory limits (103 cfu/g). Among the most agriculturally important mycotoxins, aflatoxins (B1, B2, G1, and M1) were detected in 6.3–11.9%, fumonisins (B1, B2 and B3) in 3.2–41.3%, and zearalenone in 41.3% of the samples. A few samples of improved chips, improved flour, and makopa contained high aflatoxin B1 content. Some emerging mycotoxins: emodin, beauvericin, moniliformin, sterigmatocystin, alternariol methyl ether, nivalenol, mycophenolic acid, enniatin B, and enniatin B1 were detected. The most prevalent microbial metabolites were emodin (75.4%), tryptophol (67.5%), equisetin (61.9%), and beauvericin (51.6%), at mean concentrations of 8.8 μg/kg, 794.1 μg/kg, 277.2 μg/kg, and 29.5 μg/kg, respectively. Emodin and Beauvericin are the only emerging mycotoxins in this group and the mean concentrations are the lowest. Nevertheless, regular surveillance along the cassava food chain is recommended for early detection of emerging mycotoxins to prevent health problems associated with ingestion of unexpected toxins in foods.